The relationship of maternal micronutrient intakes of Vitamin B12, vitamin B6, folate and calcium on intrauterine growth retardation and birth weight : a prospective cohort study of urban South Indian pregnant women - Dwarkanath, Pratibha (Curtin University, 2011)
The period of intrauterine growth and development is one of the most vulnerable periods in the human life cycle. The weight of the infant at birth is a powerful predictor of infant growth and survival, and is dependent on maternal health and nutrition during pregnancy. Prevention of low birth weight (LBW; <2500 g), which affects nearly 30% of infants born in India, is a public health priority. Low birth weight includes infants born prematurely (<37 weeks of gestation) or are small for gestational age (SGA; <10th % for gestational age). The majority of LBW infants in India and in most developing countries are a result of SGA. LBW is a strong predictor for size in later life because SGA infants seldom catch-up to normal size during childhood.Maternal nutrition is an important factor from a public health point of view because it is modifiable through appropriate public health interventions. In urban Indian populations, despite the routine antenatal program, there has been a high prevalence of LBW and SGA babies. Micronutrients such as vitamin B12, vitamin B6 and folate that are involved in the 1-C methyl metabolism are thought to play a key role in fetal programming. Studies have shown that vitamin B12 deficiency leads to hyperhomocysteinemia especially in populations that consume predominantly cereal based diet, as seen in India. Dietary calcium is known to be related to pregnancy - induced hypertension (PIH); a morbidity affecting ~11% of first pregnancies. PIH also increases the risk of adverse birth outcomes.I established a prospective cohort study of 637 pregnant women at St. John’s Medical College Hospital, Bangalore, India. These pregnant women were followed antenatally for their dietary intakes, health status and birth outcomes.The food frequency questionnaire (FFQ) is commonly used in epidemiological studies for assessing dietary intakes. I validated FFQ against multiple 24-hour dietary recalls (24-HDR) and observed a significant correlation between the two methods for vitamin B12, vitamin B6 and folate intakes. Correlations between the dietary intakes assessed by FFQ and the blood biomarkers (micronutrient status) indicated a good correlation between energy- adjusted vitamin B12 and micronutrient status.Intakes of vitamin B12, vitamin B6, folate and food groups rich in these vitamins were related to adverse birth outcomes. Intakes of vitamin B12 in the 1st and 2nd trimester of pregnancy correlated negatively with homocysteine (Hcy) status and positively with the birth weight. Vitamin B12 intakes also correlated negatively with Hcy concentrations in the 1st and 2nd trimester of pregnancy. I found that low intakes of cereals and dairy products in the 2nd trimester of pregnancy were associated with SGA.Evidence shows that micronutrient deficiencies exist during pregnancy indeveloping countries. In the 1st trimester approximately 50% of the pregnant women were vitamin B12 deficit, 30% had vitamin B6 deficiency and 12% with folate deficiency. Almost 38% of the subjects had elevated Hcy levels at the 1st trimester. Maternal vitamin B12 showed significant negative correlation with plasma Hcy levels within trimester after adjusting for other micronutrients. Women categorised as vitamin B12, vitamin B6 or folate deficient and those who had hyperhomocysteinemiain the 1st trimester of pregnancy had a high prevalence of adverse birth outcomes such as LBW, SGA and preterm births. High maternal plasma Hcy concentration inthe 1st trimester seemed to be a determinant of LBW after adjusting for potential confounders.Several lines of evidence show that calcium and calcium - rich food groups may play an important role in determining adverse birth outcomes particularly preterm births. I observed that mothers of preterm babies and LBW had low intakes of calcium and calcium - rich food groups. Pregnant women with PIH had significantly higher incidence of preterm births. Calcium - rich food groups include dairy products and cereals and I have seen an association between low dairy intakes and high prevalence of SGA babies. These findings suggest that combination ofnutrients as in food groups would be responsible for the adverse birth outcomes.Collectively, the results presented in this thesis indicate a preventive role for calcium in PIH and a beneficial role of specific food groups (cereals and dairy) in reducing the incidence of SGA and preterm births. Women with low maternal vitamin B12 status and hyperhomocysteinemia have higher risk of having a LBW baby. My findings would encourage interventional studies to delineate the cause effect relationship between maternal dietary / nutritional influences on maternal morbidity and birth outcomes.